Mn accumulation in a submerged plant Egeria densa (Hydrocharitaceae) is mediated by epiphytic bacteria. (20th March 2017) - Tsuji, Kousuke; Asayama, Takuma; Shiraki, Nozomi; Inoue, Shota; Okuda, Erina; Hayashi, Chizuru; Nishida, Kazuma; Hasegawa, Hiroshi; Harada, Emiko
Abstract: Many aquatic plants act as biosorbents, removing and recovering metals from the environment. To assess the biosorbent activity of Egeria densa, a submerged freshwater macrophyte, plants were collected monthly from a circular drainage area in Lake Biwa basin and the Mn concentrations of the plants were analysed. Mn concentrations in these plants were generally above those of terrestrial hyperaccumulators, and were markedly higher in spring and summer than in autumn. Mn concentrations were much lower in plants incubated in hydroponic medium at various pH levels with and without Mn supplementation than in field‐collected plants. The precipitation of Mn oxides on the leaves was determined by variable pressure scanning electron microscopy‐energy dispersive X‐ray analysis and Leucoberbelin blue staining. Several strains of epiphytic bacteria were isolated from the field‐collected E . densa plants, with many of these strains, including those of the genera Acidovorax, Comamonas, Pseudomonas and Rhizobium, found to have Mn‐oxidizing activity. High Mn concentrations in E . densa were mediated by the production of biogenic Mn oxide in biofilms on leaf surfaces. These findings provide new insights into plant epidermal bacterial flora that affect metal accumulation in plants and suggest that these aquatic plants may have use in Mn phytomining. Brief summary statement: Field‐collected Egeria densa (Brazilian waterweed, Hydrocharitaceae) plants efficiently absorbed and accumulated environmental Mn. This Mn resulted from the accumulation of biogenic Mn oxide in biofilms on the surface of the plants. Several strains of epiphytic bacteria isolated from the plants produced Mn oxide. These findings enhance understanding of aquatic plants involved in the mobilization of Mn in a freshwater environment.